UJI TOKSISITAS EKSTRAK DAUN WARU (Hibiscus tiliaceus L.) TERHADAP LARVA Artemia salina Leach SERTA IDENTIFIKASI GOLONGAN SENYAWANYA - Ni Luh Rustini; Komang Ariati; A. A. Indah Purna Dewi; I Made Dira Swantara (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
The “Brine Shrimp Lethality Test” (BSLT) is a preliminary test used to monitor the bioactive compounds from natural products as anti-cancer. This research aimed to determine of toxic compounds in the leaf of waru (Hibiscus tiliaceus L.). Maceration of 900 g waru leaf powder with 7000 mL of ethanol (5x24 hours) yielded 53,19 g ethanol extract with toxicity tests to larvae of Artemia salina Leach (LC50) of 79.43. The ethanol extract was partitioned to yield 1,81 g of n-hexane (LC50 = 63,09 ppm), 1,52 g of chloroform (LC50 = 1000 ppm) and 50,08 g of aqueous extract (LC50 = 316 ppm). The most toxic, n-hexane extract, was then separated , purified and identified. n-hexane extract was separated by column chromatography with silica gel 60 as stationary phase and n-hexane-chloroform-ethanol (5:4:1) as mobile phase to yield 7 fractions. Fraction one (F1) with a single stain on thin-layer chromatography was the most toxic (LC50 = 398 ppm). Identification with phytochemical test, UV-Vis spectrophotometer and IR spectrophotometer, showed that the isolate contained sterol compounds.